The Role of Character Education in Responding to the Challenges of the Digital Era - Delvini Febrianti; Jasiah Jasiah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The digital era presents increasingly complex ethical challenges for students, particularly due to the abundance of unfiltered information, the rapid development of instant culture, and the weakening of social supervision in everyday life. Character education has become an essential approach to equipping young generations with strong moral principles to navigate these changes. This study aims to explore the role of character education in strengthening students’ moral resilience and to identify the challenges encountered in its implementation within educational settings. This research employed a literature review method to examine various scholarly sources related to character development in the digital era. The findings indicate that character education contributes to the enhancement of students’ critical thinking skills, integrity, responsibility, and discipline in responding to digital content. However, the implementation of character education faces several obstacles, including the lack of positive role models, limited collaboration between schools and parents, and insufficient technological competencies among educators. Therefore, a comprehensive approach is required to integrate moral values into digital learning environments, improve teachers’ professional capacities, and strengthen partnerships among schools, families, and communities. Character education is thus expected to serve as an effective solution for fostering morally responsible and ethically grounded generations amid the moral challenges of the digital era.